2017
DOI: 10.1590/0102-33062017abb0214
|View full text |Cite
|
Sign up to set email alerts
|

Fructan dynamics in the underground organs of Chresta exsucca (Asteraceae), a dry season flowering species

Abstract: Climatic seasonality has an infl uence on the phenology of native Cerrado plants. Herbs and subshrubs tend to fl ower in the rainy season, although some species of these habits fl ower in the dry season. Reserve carbohydrates, stored in the underground organs, are used to support phases of high energy-demand, but also may protect plants from damage during periods of environmental limitation. In this study we evaluated variation in fructan levels in the underground organs of fi eld-grown plants of Chresta exsuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…from the genus Chresta), which occur in Cerrado sites in Serra Dourada, Goiás state, also concentrate flowering in the driest and windiest season. In another study, Santos et al (2018) also observed flowering during the dry season in Cerrado for the species Chresta exsucca D.C. in Goiás. Thus, the observed concentration of flowering and immature fruit production of C. scapigera in the dry season might be related to an anemochoric strategy to increase its pollination and dispersal success, though further study is necessary to confirm this assumption.…”
Section: Discussionmentioning
confidence: 82%
“…from the genus Chresta), which occur in Cerrado sites in Serra Dourada, Goiás state, also concentrate flowering in the driest and windiest season. In another study, Santos et al (2018) also observed flowering during the dry season in Cerrado for the species Chresta exsucca D.C. in Goiás. Thus, the observed concentration of flowering and immature fruit production of C. scapigera in the dry season might be related to an anemochoric strategy to increase its pollination and dispersal success, though further study is necessary to confirm this assumption.…”
Section: Discussionmentioning
confidence: 82%
“…Os extratos foram filtrados em filtros (0,45 μm) conectados em seringas, e em seguida foram injetados no cromatógrafo de troca aniônica de alto desempenho com detecção por pulso amperométrico (HPAEC-PAD), em conjunto pré-coluna e coluna CarboPac PA-100 (4 x 250 mm). A eluição (1 mL.min -1 ) foi realizada em gradiente de acetato de sódio em hidróxido de sódio (100 mM) com a seguinte programação: 0-10 min: 5 mM; 10,1 -35min, 5 -50 mM; 35,1 -40 min, 50 -375 mM; 40,1 -45min, 500 mM (Santos et al, 2018). Para a identificação dos açúcares foram utilizados extratos de bulbos de Allium cepa, que possui a neossérie da inulina (Yamamori et al, 2015), e de rizóforos de Chrysolaena obovata que possui a série da inulina (Carvalho; Dietrich 1993) como padrões.…”
Section: Methodsunclassified